Konsep Dasar Perancangan Wisata Gastronomi di Kecamatan Ubud, Gianyar - Anak Agung Istri Puspita Sari; Agus Kurniawan; I Wayan Wirya Sastrawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
Ubud District was proposed to be an international gastronomic tourism destination by the Ministry ofTourism and Creative Economy based on the United National World Tourism Organization (UNWTO) criteriaand was established in 2018. The Ministry of Tourism and Creative Economy also encourages the development ofcreative economic tourism based on culture and local wisdom in Ubud District to revive economic activity so thatcan expand employment opportunities in the midst of a pandemic. Gastronomic tourism is a type of culinarytourism where tourists not only consume food but can also increase their knowledge about the food and the areafrom the original source. Gastronomic development in Ubud District is less than optimal and is still limited to aplace for selling traditional culinary which only consists of one particular type of culinary at a food stall. Bydesigning gastronomic tourism in Ubud District, Gianyar will become a place for culinary activities related togastronomy and become a solution in overcoming these problems. The purpose of this study was to determine thebasic concepts that will be used in the design of gastronomic tourism in Ubud District, Gianyar. The researchmethod used is descriptive qualitative method. The results of this study produce a basic concept, namely culturaltourism based on culinary and local traditions.